2011
DOI: 10.1074/jbc.m111.225003
|View full text |Cite
|
Sign up to set email alerts
|

Lacrimal Gland Development and Fgf10-Fgfr2b Signaling Are Controlled by 2-O- and 6-O-sulfated Heparan Sulfate

Abstract: Heparan sulfate, an extensively sulfated glycosaminoglycan abundant on cell surface proteoglycans, regulates intercellular signaling through its binding to various growth factors and receptors. In the lacrimal gland, branching morphogenesis depends on the interaction of heparan sulfate with Fgf10-Fgfr2b. To address if lacrimal gland development and FGF signaling depends on 2-O-sulfation of uronic acids and 6-O-sulfation of glucosamine residues, we genetically ablated heparan sulfate 2-O and 6-O sulfotransferas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
68
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(79 citation statements)
references
References 47 publications
(40 reference statements)
7
68
2
Order By: Relevance
“…54,64,65 However, the exact role of HS in FGF signaling is still a matter of considerable debate. 33 In the present study, we found that FGF1 superfamily, FGF1/2 readily binds to FGFR1 and leads the hyper-activation of FGFR1 signaling in the absence of sulfated HSPG. In contrast, HGF/Met signaling, another well-known ligand/ receptor signaling regulated by HS, is not affected by HS sulfation status.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…54,64,65 However, the exact role of HS in FGF signaling is still a matter of considerable debate. 33 In the present study, we found that FGF1 superfamily, FGF1/2 readily binds to FGFR1 and leads the hyper-activation of FGFR1 signaling in the absence of sulfated HSPG. In contrast, HGF/Met signaling, another well-known ligand/ receptor signaling regulated by HS, is not affected by HS sulfation status.…”
Section: Discussionmentioning
confidence: 72%
“…[30][31][32] However, the exact role of HS in FGF signaling is still a matter of considerable debate. 33 In addition, how FGF signaling is tumor promoting in some contexts, but tumor-suppressive in others remains unclear. 34 In this study, we investigate the role of HS sulfation status and FGF signaling in cellular senescence.…”
mentioning
confidence: 99%
“…Lacrimal gland development (17), viability and neural development in C. elegans (18), FGF-induced signaling (19), and cartilage homeostasis (20) all depend on sulfation. Sulfation of tyrosine residues is important for the interaction of chemokines and their receptors (21)(22)(23) and for binding and entry of HIV (24).…”
mentioning
confidence: 99%
“…It has also been reported that HS6ST2 plays a critical role in mediating energy metabolism by controlling signals from the FGF-19 subfamily proteins, and that HS6ST2 dysregulation is associated with glucose and insulin intolerance (34). The deletion of HS6ST1 and HS6ST2 has been shown to disrupt the FGF-10-FGFR2b-heparan sulfate complex on the cell surface, thus demonstrating the profound effect of FGF signaling on mammalian development (35). In the present study, we demonstrated that the FGF-2-mediated chondrocyte growth and differentiation was regulated by HS6ST2, that the overexpression of HS6ST2 significantly enhanced FGF-2-mediated chondrocyte growth and differentiation, while the silencing of HSTST2 abrogated the FGF-2-mediated chondrocyte growth and differentiation.…”
Section: Discussionmentioning
confidence: 99%